A low molecular weight OLED material: 2-(4-((2-hydroxyethyl)(methyl)amino)benzylidene)malononitrile. Synthesis, crystal structure, thin film morphology, spectroscopic characterization and DFT calculations. Issue 49 (12th September 2019) - Percino, M. Judith; Cerón, Margarita; Venkatesan, Perumal; Pérez-Gutiérrez, Enrique; Santos, Pilar; Ceballos, Paulina; Castillo, Armando E.; Gordillo-Guerra, Paola; Anandhan, Karnambaram; Barbosa-García, Oracio; Bernal, Wilson; Thamotharan, Subbiah
Abstract : A low molecular weight fluorescent malononitrile derivative showed an efficient solid-state emission and electroluminescence properties. Abstract : 2-(4-((2-Hydroxyethyl)(methyl)amino)benzylidene)malononitrile (HEMABM ) was synthesized from 4-[hydroxymethyl(methyl)amino]benzaldehyde and propanedinitrile to obtain a low molecular weight fluorescent material with an efficient solid-state emission and electroluminescence properties comparable to the well-known poly(2-methoxy-5(2′-ethyl)hexoxyphenylenevinylene) (MEH-PPV ). TheHEMABM was used to prepare an organic light-emitting diode by a solution process. Despite the title compound being a small molecule, it showed optical properties and notable capacity to form a film with smooth morphology (10.81 nm) closer to that of polymerMEH-PPV (10.63 nm). The preparation of the device was by spin coating, the electrical properties such as threshold voltage were about 1.0 V for bothHEMABM andMEH-PPV, and the luminance 1300 cd m −2 forHEMABM and 2600 cd m −2 forMEH-PPV . This low molecular weight compound was characterized by SCXRD, IR, NMR, and EI. Besides a quantitative analysis of the intermolecular interactions by PIXEL, density functional theory (DFT) calculations are reported.